HUBUNGAN ASUPAN NUTRISI TERHADAP PENGONTROLAN KADAR HEMOGLOBIN PASIEN HEMODIALISIS DI MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Pasaribu, Petrus P.; Silaen, Harsudianto (Excellent Midwifery Journal, 2024)
Anemia is often found in patients with chronic kidney disease, especially in patients with advanced chronic kidney disease undergoing hemodialysis therapy. Anemia is influenced by factors such as age, gender, and duration of hemodialysis, as well as nutritional factors. Insufficient nutritional intake is often experienced by patients with chronic kidney disease undergoing dialysis therapy. The purpose of this study was to determine the relationship between nutritional intake and hemoglobin level control in hemodialysis patients at Murni Teguh Memorial Hospital Medan. This study used a quantitative research method with a cross-sectional design and used a sampling technique, namely purposive sampling. The test used in this study was the Chi-Square test. The results of the study showed that there was a relationship between nutritional intake and hemoglobin level control in hemodialysis patients with a p value = 0.005 or p <0.05. The conclusion of the study is that there is a significant relationship between nutritional intake and hemoglobin level control in hemodialysis patients. It is expected that patients are able to know the types of food and the amount of food needed by their bodies every day so that with sufficient nutritional intake, the patient's hemoglobin level is also expected to be within normal limits.